Seed Dispersal: Theory and Its Application in a Changing World 2007
DOI: 10.1079/9781845931650.0078
|View full text |Cite
|
Sign up to set email alerts
|

A review on the role of endozoochory in seed germination.

Abstract: This chapter evaluates the role of endozoochory on seed germination and reviews the information gathered on germination patterns in experiments aimed at examining the effect of a seed's passage through a frugivore's gut, and gives further directions on methods for future studies. Most data demonstrating the different mechanisms by which frugivores can affect seed fate are from studies performed with birds and mammals, which are the numerically dominant dispersers in many systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
250
4
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 195 publications
(273 citation statements)
references
References 68 publications
4
250
4
6
Order By: Relevance
“…Nevertheless, mist-netting is likely the best method to construct quantitative seed dispersal networks as it is largely free of observer bias and allows great taxonomic resolution (species level with few exceptions), allows the detection of inconspicuous dispersers and interactions, makes the study of individual food choice possible through individual marking (e.g. rings), and allows the evaluation of the effect of seed ingestion on its viability (Costa et al 2014;Traveset, Robertson, & Rodríguez-Pérez 2007;Heleno, Ross, Everard, Memmott, & Ramos 2011).…”
Section: Network Propertiesmentioning
confidence: 99%
“…Nevertheless, mist-netting is likely the best method to construct quantitative seed dispersal networks as it is largely free of observer bias and allows great taxonomic resolution (species level with few exceptions), allows the detection of inconspicuous dispersers and interactions, makes the study of individual food choice possible through individual marking (e.g. rings), and allows the evaluation of the effect of seed ingestion on its viability (Costa et al 2014;Traveset, Robertson, & Rodríguez-Pérez 2007;Heleno, Ross, Everard, Memmott, & Ramos 2011).…”
Section: Network Propertiesmentioning
confidence: 99%
“…Both in nature and in nurseries, poor, unreliable seed germination is common (Catalán, 1991;Traveset et al, 2007). The genus Phillyrea produces blue-black drupes, usually containing a single seed, which are dispersed by animals, such as goats and birds (Herrera et al, 1998;Traveset et al, 2007;Andrés, 2011). Due to their lignified endocarp, it has been suggested that Phillyrea seeds might have physical dormancy (García-Fayos et al, 2001;Takos & Efthimiou, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these studies described vertebrates (reptiles, birds and mammals) as dispersers of plant seeds. Other interactions, like secondary dispersal and predation, have scarcely been included in ecological seed studies in southern Chile, and few studies have included the effect of seed consumption by vertebrates in seed germination , Soto-Gamboa & Bozinovic 2002, Traveset et al 2006, Reid & Armesto 2011.…”
Section: Introductionmentioning
confidence: 99%